Mesoporous Inorganic Membrane Reactor for Oxidative Coupling of Methane - N.C May; A.R Mohamed; S Bhatia (Universitas Gadjah Mada, 2004)
The mesoporous inorganic membrane has been developed and characterized for oxidative coupling of methane reactions. In this research, g-alumina membrane was modified with Lanthanum. The membrane has shown thermal stability in prolonged exposure to the high-temperature application of 600-900°C. The results were confirmed by TGA and OCM experimentations. TGA results showed only 2-3% loss from an initial weight that is mainly due to evaporation of water and release of the nitrate compound. The membrane was also found stable for at least a month of operationwhile the catalyst was being regenerated to regain its activity. The SEM cross-sections show successful deposition of Lanthanum in spite of its non-uniform deposition layer and crack formation.